Members only: the Victorian gentlemen's club as a space for doing business 1843–1900. Issue 2 (3rd April 2019) - Joseph, Marrisa
ABSTRACT: This paper examines how the gentlemen's club was a space for facilitating business activities in the literary publishing industry of Victorian Britain. These clubs served to blur the boundaries between the social and professional sphere, to the point that many used the club as hub for networking and for providing opportunities. The gentlemen's clubs of London have been examined within gender studies and in studies on social culture, where emphasis has been placed on its role in elite and middle-class society and its influence on gender and class inequality. However, little attention has been dedicated in academic business research to the club's influence on shaping the activities of businesses in the publishing industry. By exploring how individuals engaged with so-called 'club life, ' it is possible to analyze the dynamics of how and why gentlemen's clubs were important to literary businesses. Through an exploration of narrative and documentary archival sources, this paper explores the perspective and choices of individuals working in the publishing industry, and the extent to which their choices in business were governed by the cultural influences of the gentlemen's club.